Predicting success: The effect of pre-target cueing on inhibition performance. - GARAVAN, HUGH PATRICK (MIT Press, 2004)
The present study investigated the relationships between attention and other preparatory processes prior to a response inhibition task and the processes involved in the inhibition itself. To achieve this, a mixed fMRI design was employed to identify the functional areas activated during both inhibition decision events and the block of trials following a visual cue introduced 2 to 7 sec prior (cue period). Preparing for suc- cessful performance produced increases in activation for both the cue period and the inhibition itself in the frontoparietal cortical network. Furthermore, preparation produced activa- tion decreases in midline areas (insula and medial prefrontal) argued to be responsible for monitoring internal emotional states, and these cue period deactivations alone predicted sub- sequent success or failure. The results suggest that when cues are provided to signify the imminent requirement for be- havioral control, successful performance results from a co- ordinated pattern of preparatory activation in task-relevant areas and deactivation of task-irrelevant ones.
PUBLISHED
Keywords: Psychology